(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present study was focused to develop and optimize a gastro retentive drug delivery system (GRDDS) dosage form suitable for controlled drug release. Gastroretention results from unfolding and swelling of the film and its bioadhesion to the gastric mucosa. Hydralazine hydrochloride (HZH) is very short and thus it requires frequency of dosing several times a day. Hence, in order to avoid frequent administrations, a long acting mucoadhesive oral dosage forms can be given which can keep on delivering the drug at controlled rate for a specified period of time. A mucoadhesive drug delivery systems is an optimum system that interacts with the mucus layer covering the mucosal epithelial surface and increase the residence time of the dosage form at the absorption site. A sustained release mucoadhesive gastro-retentive with reduced dosing frequency and increased drug bioavailability is developed. Inclusion of different polymers like hydroxy propyl methyl cellulose K4M (HPMC K4M), carbopol 940 and sodium alginate at different concentration were used in order to study and get desired results. The results indicate the dosage form is gastroretentive and can provide controlled release of drugs with a release drug profile upto 24 hours. The above said formulation was further optimized using box-behnken factorial design.